Golden age the revitalized PTV-4 headquarters and studio - Bautista, Ida Isobel C.; Bo-ot, Luis, Ma. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
In the era of the late 2010s, broadcasting media has been inundated with the problem of fake news and the propagation of false information. This thesis study takes that issue and address it through the revitalization of the Philippine Government's official broadcasting network, the People's Television Network, or PTV-4. Through the modernization, streaming, and rebranding of the network's main studio and headquarters, critical minds with a passion to change the world of journalism in a positive way will be attracted to become part in the execution of the unique role of PTV-4 in Philippine Broadcasting. The changes made to the current headquarters and studio shall also widen the network's reach, thereby increasing its impact on its target audience.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Broadcasting network -- Philippines